Diversity and assessment of economic plants of Tehsil Takht Bhai, district Mardan, Pakistan - Parveen, Sadia; Ullah, Asad (Ethnobotany Research and Applications, 2023)
Background: Plants play a vital role in the maintenance and economic development of an area. The current research work focuses on the investigation of economic tree species of Tehsil, Takht Bhai, and District Mardan. Methods: For data collection different localities of Tehsil Takht Bhai were visited during 2021-2022. The plants were dried and identified with the help of Flora of Pakistan. Representative plant parts were mounted on herbarium sheets and submitted to herbarium of Center of Plant Biodiversity, University of Peshawar. The data for fuel wood was collected through standard procedures of ex-situ (artifact) and in-situ (inventory) methods. Wood depots, sawmills and farmers were visited, and information was collected from fruit markets, furniture industry, timber markets, and construction material owners through a questionnaire on the spot by interview method. The calorific value of fuel wood species was determined by Bomb Calorimeter. Results: The plants were evaluated for their conservation status in which 7 spp. were exotic, 5 spp. were indigenous, 9 spp. were not evaluated, 2 spp. were of least concern and Acacia nilotica (L.) Willd. ex Delile was critically endangered. A total of 360000 mounds of fuel wood was sold out in summer season resulted into a revenue of PKR 241.2 million (m). The highest sale of 90000 mounds was recorded in case of Populus euramericana (Dode) Guinier, which generated 63 m of revenue. In winter season 438000 mounds of fuel wood was sold out that generated revenue of PKR 340.2 m. The highest sale of 105000 mounds was recorded in case of P. euramericana, which generated PKR 94.50 m of revenue. Maximum per annum revenue of PKR 157.50 m was generated from selling of P. euramericana. On priority basis, 50 % of the local people used Acacia modesta Wall. as fuel wood and 55 % of people used Dalbergia sissoo Roxb. ex DC. for furniture. The maximum income generated from fuel wood on basis of consumption priority was PKR 35.1 m and for furniture was PKR 33.66 m for these species respectively. It was also noted that P. euramericana was used for formation of pallets, which generates revenue of PKR 720 m per annum from 10 sites. Other economic uses include fodder (8 spp.), fruits (2 spp.), furniture (10 spp.), timber (10 spp.), constructional material (11 spp.), bed legs (7 spp.), chip boards (3 spp.), match industry (2 spp.), sport items (2 spp.), toothpicks (2 spp.), ice-cream sticks and pallets (1 sp.) each. The calorific value showed that A. modesta had highest value i.e., 5500 kcal/kg while Ailanthus altissima (Mill.) Swingle had lowest value i.e., 4400 kcal/kg. P. euramericana and Eucalyptus camaldulensis Dehn. were adopted by the locals as farm and agro forestry species. Conclusion: From the current research, it was concluded that the inhabitants of the area rely heavily on plants for fuel wood as well as other economic purposes and also gain high revenue generation so sustainable use of plants should be made in order to support the socio-economic status of the local inhabitants. Key words: Assessment, diversity, economic plants, fuel wood, Mardan, Pakistan, Takht Bhai.